Social media : influences on education - Griffin, Marlynn M.; Zinskie, Cordelia D. (Current perspectives on cognition, learning, and instruction., 2021)
"Social media is a multi-faceted tool that has been used by educators and/or their students in ways both beneficial and detrimental. Despite the ubiquitous nature of this tool, there is much research still needed on the multitude of ways that social media impacts education. This book presents research on the influences of social media on education, broadly construed. Specifically, the research included in this book is categorized into four broad areas, examining the educational influence of social media on youth and college students, professional development in content areas, higher education learning, and social justice and activism. Chapter authors emphasize the opportunities of social media use in education and provide recommendations for how to address challenges that may arise with social media integration into the teaching and learning setting. These authors also advocate for use of social media to grow and enhance professional interaction among educators, moving beyond the social aspect of these platforms to advocate for educational and societal change. Individuals working in K-12 schools, teacher education, teacher professional development, and higher education, including pharmacy, nursing, dental and medical education, as well as those in other educational settings can use these findings to support and guide integration of social media into teaching and learning as well as their professional practice"--